On Kalman Smoothing for Wireless Sensor Networks Systems with Multiplicative Noises - Xiao Lu; Haixia Wang; Xi Wang (Journal of Applied Mathematics)
The paper deals with Kalman (or H2) smoothing problem for wireless sensor networks (WSNs) with multiplicative noises. Packet loss occurs in the observation equations, and multiplicative noises occur both in the system state equation and the observation equations. The Kalman smoothers which include Kalman fixed-interval smoother, Kalman fixedlag smoother, and Kalman fixed-point smoother are given by solving Riccati equations and Lyapunov equations based on the projection theorem and innovation analysis. An example is also presented to ensure the efficiency of the approach. Furthermore, the proposed three Kalman smoothers are compared.